NEWS2’ as an objective assessment of hospitalised COPD exacerbation severity - Stone,P; Minelli,C; Feary,J; Roberts,CM; Quint,J; Hurst,JR (International Journal of COPD, 2022)
Introduction: There is currently no accepted way to risk-stratify hospitalised exacerbations of chronic obstructive pulmonary disease (COPD). We hypothesised that the revised UK National Early Warning Score (NEWS2) calculated at admission would predict inpatient mortality, need for non-invasive ventilation (NIV) and length-of-stay.Methods: We included data from 52,284 admissions for exacerbation of COPD. Data were divided into development and validation cohorts. Logistic regression was used to examine relationships between admission NEWS2 and outcome measures. Predictive ability of NEWS2 was assessed using area under receiver operating characteristic curves (AUC). We assessed the benefit of including other baseline data in the prediction models and assessed whether these variables themselves predicted admission NEWS2.Results: 53% of admissions had low risk, 24% medium risk and 23% a high risk NEWS2 in the development cohort. The proportions dying as an inpatient were 2.2%, 3.6% and 6.5% by NEWS2 risk category, respectively. The proportions needing NIV were 4.4%, 9.2% and 18.0%, respectively. NEWS2 was poorly predictive of length-of-stay (AUC: 0.59[0.57– 0.61]). In the external validation cohort, the AUC (95% CI) for NEWS2 to predict inpatient death and need for NIV were 0.72 (0.68– 0.77) and 0.70 (0.67– 0.73). Inclusion of patient demographic factors, co-morbidity and COPD severity improved model performance. However, only 1.34% of the variation in admission NEWS2 was explained by these baseline variables.Conclusion: The generic NEWS2 risk assessment tool, readily calculated from simple physiological data, predicts inpatient mortality and need for NIV (but not length-of-stay) at exacerbations of COPD. NEWS2 therefore provides a classification of hospitalised COPD exacerbation severity.